The design of user-defined packaging as a tool to educate visual education students - Yeo, Jesvin Puay-Hwa (2015)
The purpose of this paper is two-fold: 1) to depict an experimental journey to understand inclusive packaging design and 2) to present an investigation of how visual communication students used packaging design as a platform to understand user-friendly design. Twenty-one students were asked to design a package with technology device(s) or non-packaging materials that can facilitate daily life by focusing on senses, sensitivity, and sensibility. The objective was to identify problems in packaging, redefine the parameters, and guide the design of senior-friendly solutions. The students were asked to explore ways in which design could help enhance the experiences of growing old and create solutions that consider senior-friendly design. The study covered three areas: user-based research, packaging research, and strategic design development. Students discussed and observed packaging difficulties of daily life. When an item was identified, users were interviewed to highlight specific problems. Packaging, materials, and manufacturing processes were also studied in parallel to promote innovative solutions. A total of 21 items were selected for redesign development. This paper describes the student projects, the process, and the learning outcomes.